Inhibition of fibroblast secreted QSOX1 perturbs extracellular matrix in the tumor microenvironment and decreases tumor growth and metastasis in murine cancer models - Feldman, Tal (Oncotarget, 2020)
Extracellular matrix (ECM) plays an important role in tumor development and dissemination, but few points of therapeutic intervention targeting ECM of the tumor microenvironment have been exploited to date. Recent observations suggest that the enzymatic introduction of disulfide bond cross-links into the ECM may be modulated to affect cancer progression. Specifically, the disulfide bond-forming activity of the enzyme Quiescin sulfhydryl oxidase 1 (QSOX1) is required by fibroblasts to assemble ECM components for adhesion and migration of cancer cells. Based on this finding and the increased QSOX1 expression in the stroma of aggressive breast carcinomas, we developed monoclonal antibody inhibitors with the aim of preventing QSOX1 from participating in pro-metastatic ECM remodeling. Here we show that QSOX1 inhibitory antibodies decreased tumor growth and metastasis in murine cancer models and had added benefits when provided together with chemotherapy. Mechanistically, the inhibitors dampened stromal participation in tumor development, as the tumors of treated animals showed fewer myofibroblasts and poorer ECM organization. Thus, our findings demonstrate that specifically targeting excess stromal QSOX1 secreted in response to tumor-cell signaling provides a means to modulate the tumor microenvironment and may complement other therapeutic approaches in cancer.